2021
DOI: 10.1111/apt.16727
|View full text |Cite
|
Sign up to set email alerts
|

Skipping breakfast is associated with an increased long‐term cardiovascular mortality in metabolic dysfunction‐associated fatty liver disease (MAFLD) but not MAFLD‐free individuals

Abstract: Background: Balancing calorie control to prevent cardiovascular diseases (CVDs) by skipping breakfast while guarding against its potential risks is a challenge. Aims:To explore the association between skipping breakfast and cardiovascular mortality in individuals with metabolic dysfunction-associated fatty liver disease (MAFLD).Methods: A total of 9926 individuals (including 3004 MAFLD participants) aged 20 years or older were enrolled in the Third National Health and Nutrition Examination Survey and followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Similarly, in 194 patients with type-2 diabetes mellitus who do not work shift work, a late chronotype was associated with skipping breakfast ( p = 0.014) [ 109 ]. In fact, it has been demonstrated that frequent breakfast skipping was independently associated with higher cardiovascular mortality risk ( p < 0.001) in 3004 participants with metabolic associated fatty liver disease (MAFLD), but not in MAFLD-free individuals ( p = 0.280) [ 110 ].…”
Section: Chrononutrition In the Management Of Nafldmentioning
confidence: 99%
“…Similarly, in 194 patients with type-2 diabetes mellitus who do not work shift work, a late chronotype was associated with skipping breakfast ( p = 0.014) [ 109 ]. In fact, it has been demonstrated that frequent breakfast skipping was independently associated with higher cardiovascular mortality risk ( p < 0.001) in 3004 participants with metabolic associated fatty liver disease (MAFLD), but not in MAFLD-free individuals ( p = 0.280) [ 110 ].…”
Section: Chrononutrition In the Management Of Nafldmentioning
confidence: 99%
“…The authors' declarations of personal and financial interests are unchanged from those in the original article. 5…”
Section: Ack N Owled G M Entsmentioning
confidence: 99%
“…We have read the cohort study by Xie et al regarding the metabolic dysfunction-associated fatty liver disease (MAFLD) in the health database using the National Health and Nutrition Examination Survey (NHANES) with great interest. 1 The authors pointed out the association between skipping breakfast and long-term cardiovascular mortality in MAFLD individuals. We appreciate the valuable contribution of the authors to clarifying the possible underlying causes of the disease in the health database.…”
Section: Editorsmentioning
confidence: 99%
“…The authors defined MAFLD using strict criteria, including abdominal ultrasound diagnosed-hepatic steatosis in addition to one of the following three conditions: (a) overweight/ obesity (BMI ≥23 kg/m 2 ); (b) presence of type 2 diabetes mellitus and (c) lean/normal weight with two metabolic dysregulations. 1 However, considering that the majority ethnicity in NHANES is Caucasians, the definition of overweight/obesity as BMI ≥23 kg/m 2 might be inappropriate. Besides, according to the MAFLD definition suggested by Eslam et al, overweight or obesity were defined as BMI ≥25 kg/m 2 in Caucasians.…”
Section: Editorsmentioning
confidence: 99%